A Case of Peripherally Induced Task-Specific “Lipstick Dystonic Tremor” - Francesco Cavallieri (Tremor and Other Hyperkinetic Movements, 2019)
Background: Peripherally induced movement disorders (PIMDs) represent a rare and debated complication of peripheral trauma. Phenomenology Shown: We report a case of task-specific “lipstick” jerky dystonic tremor as a consequence of traumatic shoulder injury, successfully treated with EMG-guided botulinum toxin injections. Educational Value: This case expands the phenotypic spectrum of PIMDs, with a visual example of a task-specific dystonic tremor after peripheral trauma, and the efficacy of EMG-guided botulinum toxin treatment in the setting of posttraumatic dystonic tremor.